Demonstrations of violence in students of the Universidad Autónoma Indígena de México - Romero Castro, María del Rosario (Yachay, 2023)
The manifestations of violence are attitudes that are immersed in all the contexts in which living beings coexist. These have been present throughout human history; therefore, experts have proposed various ways and methods to stop it, however, the escalation of violence in all its manifestations has reached unusual levels. In this sense, university contexts are not immune to this phenomenon, therefore, the objective of this research is to describe the various forms of violence that exist in the Universidad Autónoma Indígena de México (UAIM), located in the State of Sinaloa, Mexico. 167 sixth semester students and 4 teachers from the Mochicahui Unit participated in the research. The methodology applied has a mixed approach; The results were achieved by applying a survey to students and conducting interviews with the coordinators of the educational programs. It was found that 76% of the students surveyed report that the main form of violence is verbal, considered as direct violence; to a lesser extent, forms of cultural violence due to discrimination and perceived structural violence due to abuse of authority by teachers were found. Given this, it is urgent to stimulate actions to solve the problem of violence suffered by millions of citizens of the world. The bet of government agencies and civil society is in education for the development of skills in conflict management, violence prevention and to learn to build spaces of peace.